THE UTILIZATION OF WOODEN SKIN Acacia Mangium AS RAW MATERIAL OF PARTICLE BOARDS USING RESIN AMBER - Rido Sukmawi; Rudianda Sulaeman; Evi Sribudiani (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2020)
Acacia Mangium bark waste is an alternative form of raw material that can be used as a raw material in making particle board. Acacia Mangium skin has wood components ranging from 10.5 - 12.1%, while the adhesive used is resin 70% mixed with solar oil 30%. Making particle board with a size of 25 cm x 20 cm x 2 cm with a particle size of 4 mesc with boiling method of raw materials and drying, pressing for 8 hours and conditioning for 20 days. The purpose of this study was to determine the physical and mechanical properties of the particle board, using 3 samples and 3 replications for each test, the data obtained then averaged then the results compared with the characteristics of SNI 03-2105-2006. Based on the results of the research on physical properties, namely density 0.91 gr/cm3, moisture content 11.91%, water absorption 65.12% and development thickness of 16.39% while the mechanical properties are MOE 1.70 104 kgf/cm2 and MOR 27,62 kgf/cm2.